Implementasi Kebijakan Pemanfaatan Barang Milik Negara: Inklusi dan Peluang Ekonomi Bagi Pelaku Usaha Ultra Mikro, Mikro, dan Kecil di Provinsi Daerah Khusus Ibu Kota Jakarta - Alamsyah, Rachmat; Nurasa, Heru; Candradewini, Candradewini (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2025)
The policy on the utilization of State-Owned Assets (SOA) in the form of land and/or buildings opens up opportunities for the public to use these assets for business ventures. The policy for utilizing SOA is regulated under the Minister of Finance Regulation No. 115/PMK.06/2020 on the Utilization of SOA. Notably, there is a provision that offers a tariff reduction for the use of SOA for ultra-micro, micro, and small enterprises (UMMS). This research aims to examine how the policy on tariff reductions for SOA utilization is implemented for UMMS. The study was conducted using a qualitative method. The research reveal that the implementation of the policy is underway, though some improvements are needed. Analysis of four key factors for the successful implementation identifies three main challenges: tax compliance, a shortage of human resources, and limited access to information on the availability of SOA land and/or buildings that can be utilized.